2021
DOI: 10.1055/s-0041-1725014
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Biomechanical Assessment of a Novel Multi-Strand Repair of Canine Tendon Lacerations

Abstract: Objective This study aimed to evaluate the effect of increasing the number of suture strands traversing the transection site, level of suture purchase and depth of suture penetrance on the biomechanical properties of repaired gastrocnemius tendons. Study Design Thirty-eight adult cadaveric gastrocnemius tendons were randomized, transected and repaired with either two-, four- or six-strand locking multi-level repair. Tensile loads required to create a 1 and 3 mm gap, yield, peak and failure loads and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
(189 reference statements)
0
4
0
Order By: Relevance
“…3,4 The strength of the primary repair of the tendon is improved by increasing the number of suture strands crossing the repair, increasing points of suture purchase from the transection site, and depth of suture penetrance. 24,25 This is obtained using locking-loop, three-loop pulley, and Krackow suture patterns. Furthermore, the three-loop pulley is considered to be the suture pattern of choice for rounded-tendon primary repair.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 The strength of the primary repair of the tendon is improved by increasing the number of suture strands crossing the repair, increasing points of suture purchase from the transection site, and depth of suture penetrance. 24,25 This is obtained using locking-loop, three-loop pulley, and Krackow suture patterns. Furthermore, the three-loop pulley is considered to be the suture pattern of choice for rounded-tendon primary repair.…”
Section: Discussionmentioning
confidence: 99%
“…Several human and veterinary studies [18][19][20][21][22] have shown that improvements in tensile strength can be achieved by increasing the number of suture strands or suture loops traversing the tenorrhaphy. As a result, many techniques used for distal extremity tendon repair in humans have led to an increase in pattern complexity and resultant use of multistrand repair patterns.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, many techniques used for distal extremity tendon repair in humans have led to an increase in pattern complexity and resultant use of multistrand repair patterns. 19,20,22 In a study using an ovine tendon model Al-Qattan et al 20 demonstrated an approximately 2-fold increase in repair site strength when increasing from a 2 to 6 strand repair method. Recent literature has demonstrated similar findings in veterinary studies 21,23 evaluating mid body repair following laceration of canine tendons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation